Tantalum nanoparticles enhance the osteoinductivity of multiscale composites based on poly(lactide-co-glycolide) electrospun fibers embedded in a gelatin hydrogel. (June 2022) - Liguori, A.; Gino, M.E.; Panzavolta, S.; Torricelli, P.; Maglio, M.; Parrilli, A.; Gualandi, C.; Griffoni, C.; Barbanti Brodano, G.; Fini, M.; Focarete, M.L.
Abstract: Bioresorbable polymeric materials have risen great interest as implants for bone tissue regeneration, since they show substantial advantages with respect to conventional metal devices, including biodegradability, flexibility, and the possibility to be easily modified to introduce specific functionalities. In the present work, an innovative nanocomposite scaffold, properly designed to show biomimetic and osteoinductive properties for potential application in bone tissue engineering, was developed. The scaffold is characterized by a multi-layer structure, completely different with respect to the so far employed polymeric implants, consisting in a poly(d, l -lactide-co-glycolide)/polyethylene glycol electrospun nanofibrous mat sandwiched between two hydrogel gelatin layers enriched with tantalum nanoparticles (NPs). The composition of the electrospun fibers, containing 10 wt% of polyethylene glycol, was selected to ensure a proper integration of the fibers in the gel phase, essential to endow the composite with flexibility and to prevent delamination between the layers. The scaffold maintained its structural integrity after six weeks of soaking in physiological solutions, albeit the gelatin phase was partially released. The combined use of gelatin, bioresorbable electrospun fibers and tantalum NPs endows the final device with biomimetic and osteoinductive properties. Indeed, results of the in vitro tests demonstrate that the obtained scaffolds clearly represent a favorable milieu for normal human bone-marrow derived mesenchymal stem cells viability and osteoblastic differentiation; moreover, inclusion of tantalum NPs in the scaffold improves cell performance with particular regard to early and late markers of osteoblastic differentiation. Graphical abstract: Image 1 Highlights: PLGA fibers are embedded in a hydrogel containing tantalum nanoparticles. The potential for bone tissue regeneration is assessed through in vitro tests. Tantalum nanoparticles enhance the osteoinductivity of the multiscale composite.